JAMINAN TUHAN KEPADA GIDEON SERTA IMPLIKASINYA TERHADAP ORANG PERCAYA: STUDI HERMENEUTIK BERDASARKAN HAKIM-HAKIM 6:23 - Aska Aprilano Pattinaja; Endah Totok Budoyono (Phronesis: Jurnal Teologi dan Misi, 2024)
The Lord's word of assurance to Gideon in Judges 6:23 contains three things, namely, "be sure," "do not be afraid," and "you will not die. The two main problems with this verse are, first, that these words of the Lord are in stark contrast to the reality that Gideon faced, which was fearful and desperate, so he doubted the promise. For this reason, it is necessary to investigate God's ultimate motive in giving this assurance. Secondly, the phrase "you shall not die" contradicts the narrative that explains Gideon's death, so it must be described in detail. This problem is precisely and comprehensively explored and researched to explain this verse adequately. Thus, based on the descriptive qualitative research method with a hermeneutic study with a micro-analytical exegesis approach, this study found several things, namely, first, God's guarantee of salvation; second, God's guarantee of not being afraid; and third, God's guarantee of preserving and protecting the life of every believer. This article contributes to scholars, servants of God, and theological activists to better understand the story of Gideon in Judges.